EFL College Students’ Perception on Physical and Psychological Aspects toward the Use of Cake Application as Autonomous Learning Activitiy - Ranger, Raply; Marlina, Leni (Journal of English Language Teaching, 2024)
The perceptions of English as a Foreign Language (EFL) college students regarding the Cake Application vary depending on their proficiency levels, with both low and high-ability students having distinct viewpoints. The Cake Application, known for its accessible features, serves as a convenient tool for English learning, particularly for those seeking autonomous learning opportunities. This study aims to explore how students perceive the Cake Application as a means to enhance motivation in learning English. Using a descriptive quantitative approach, the research was conducted among students enrolled in the Advanced Listening class at Universitas Negeri Padang, Faculty of Language and Arts. The sample comprised 29 students from the K5 Advanced Listening class within the English Language Education Program. Employing a total sampling technique, data were collected through a questionnaire consisting of 8 closed statements rated on a 4-point Likert scale. The findings indicated positive perceptions across various aspects, encompassing both physical and psychological dimensions, with an overall mean score of 3.15. Based on these encouraging results, it is recommended for other classes to consider adopting the Cake Application as an autonomous learning tool to enrich English learning experiences.